Struggling to the heard : South Asian Muslim voices - Sikkand, Yogindar, 1967- (New Delhi : Global Media publications, 2004)
Transcript of interviews with selected Muslim leaders and thinkers from India and Pakistan
Keywords: Muslims -- India -- Interviews; Muslims -- Pakistan -- Interviews